Componential Analysis of The Cultural Terms in The Bilingual Short Story Entitled Mati “Salah Pati” and Its Translation “The Wrong Kind of Death” - Arnita, I Gusti Ayu; Puspani, Ida Ayu Made; Seri Malini, Ni Luh Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): March 2016)
This research aims at identifying the cultural terms in the bilingual text Mati “Salah Pati” and its translation “The Wrong Kind of Death”. Futhermore this research also discusses about componential analysis of Balinese cultural term and its translation to English from foreign point of view. The componential refers to the description of the meaning of words through structured sets of semantic features, which are given as “present (+)”, “absent (-)” or “indifferent with reference to feature (+/-)”. This research used descriptive qualitative method since the objectiveness of this research is closely related to identifying and describing the result of the analysis. The data source of this research was taken from a bilingual short story entitled Mati “Salah Pati”, written by Gde Aryantha Soethama and its translation entitled “The Wrong Kind of Death” translated By Jennifer Lindsay. The result of the analysis shows that componential analysis in translation is the basic comparison of a source language word with a target language word which has a similar meaning, but not an obvious one-to-one equivalent, by demonstrating first their common and then their differing sense components. From the four basic types of semantic features, there are two types of semantic features can be found in this study, those are object element and event element. Componential analysis also shows that no word has the exactly same feature and same meaning, it is depend on the culture of the community
Keywords: componential analysis, comparison, Balinese cultural terms, meaning